MTORC1 signalling is not essential for the maintenance of muscle mass and function in adult sedentary mice. Issue 1 (7th November 2019) - Ham, Alexander S.; Chojnowska, Kathrin; Tintignac, Lionel A.; Lin, Shuo; Schmidt, Alexander; Ham, Daniel J.; Sinnreich, Michael; Rüegg, Markus A.
Abstract: Background: The balance between protein synthesis and degradation (proteostasis) is a determining factor for muscle size and function. Signalling via the mammalian target of rapamycin complex 1 (mTORC1) regulates proteostasis in skeletal muscle by affecting protein synthesis and autophagosomal protein degradation. Indeed, genetic inactivation of mTORC1 in developing and growing muscle causes atrophy resulting in a lethal myopathy. However, systemic dampening of mTORC1 signalling by its allosteric inhibitor rapamycin is beneficial at the organismal level and increases lifespan. Whether the beneficial effect of rapamycin comes at the expense of muscle mass and function is yet to be established. Methods: We conditionally ablated the gene coding for the mTORC1‐essential component raptor in muscle fibres of adult mice [inducible raptor muscle‐specific knockout (iRAmKO)]. We performed detailed phenotypic and biochemical analyses of iRAmKO mice and compared them with muscle‐specific raptor knockout (RAmKO) mice, which lack raptor in developing muscle fibres. We also used polysome profiling and proteomics to assess protein translation and associated signalling in skeletal muscle of iRAmKO mice. Results: Analysis at different time points reveal that, as in RAmKO mice, the proportion of oxidative fibres decreases, but slow‐type fibres increase in iRAmKO mice. Nevertheless, no significant decrease in body and muscle mass or muscle fibre area was detected up to 5 months post‐raptor depletion. Similarly, ex vivo muscle force was not significantly reduced in iRAmKO mice. Despite stable muscle size and function, inducible raptor depletion significantly reduced the expression of key components of the translation machinery and overall translation rates. Conclusions: Raptor depletion and hence complete inhibition of mTORC1 signalling in fully grown muscle leads to metabolic and morphological changes without inducing muscle atrophy even after 5 months. Together, our data indicate that maintenance of muscle size does not require mTORC1 signalling, suggesting that rapamycin treatment is unlikely to negatively affect muscle mass and function.